Bamboo salt has in vitro anticancer activity in HCT-116 cells and exerts anti-metastatic effects in vivo - Zhao, Xin; Kim, So-Young; Park, Kun-Young (Journal of medicinal food, 2013)
Bamboo salt is a traditional food widely used in Korea. The in vitro anticancer effects of this salt were evaluated in HCT-116 human colon cancer cells using a 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyltetrazolium bromide (MTT) assay. A 1% salt concentration of bamboo salt baked nine times (9×) inhibited the growth of HCT-116 cells by 53%, which was higher than salt baked three times (3×) or once (1×; 44% and 41%, respectively) and much higher than solar sea salt (Korean sea salt) and purified salt (22% and 18%, respectively). To elucidate the inhibitory mechanisms underlying the anticancer effect of the salt samples in cancer cells, expression of genes associated with apoptosis, inflammation, and metastasis was measured with reverse transcription-polymerase chain reaction and Western blotting. Bamboo salt (9×) significantly induced apoptosis in cancer cells (P<.05) by upregulating Bax, caspase-9, and caspase-3, and downregulating Bcl-2. The expression of genes associated with inflammation (NF-κB, iNOS, and COX-2) was significantly downregulated (P<.05) by 9× bamboo salt, demonstrating its anti-inflammatory properties. The 9× bamboo salt also exerted a greater anti-metastatic effect on cancer cells than the other salts as demonstrated by decreased mRNA expression of MMP genes and increased expression of tissue inhibitors of metalloproteinases, which was confirmed by the inhibition of tumor metastasis induced in colon 26-M3.1 cells in BALB/c mice. In contrast, purified and solar salts increased metastasis in the mice. Our results demonstrated that 9× bamboo salt had the most potent in vitro anticancer effect, induced apoptosis, had anti-inflammatory activities, and exerted in vivo anti-metastatic effects. Additionally, the anticancer, anti-inflammatory, and anti-metastatic effects of the 1× and 3× bamboo salts were stronger than those of the purified and solar salts.